Answer:
im pretty sure its undefined
Step-by-step explanation:
I'd say this because i don't believe you can do anything with the info they give you
Answer: -30
Step-by-step explanation:
My answer is correct because, All you have to do is subtract all the numbers by 11 and the one that has the sum -19 is the correct choice. In this case -30 does and we can make sure were orrect by subtracting 11 by -19 and that equals -30.
#![AnimePower](https://tex.z-dn.net/?f=AnimePower)
Answer:
The expression to this question is "
".
Step-by-step explanation:
Answer:
scale factor = 3
Step-by-step explanation:
The scale factor is the ratio of corresponding sides, larger to smaller.
scale factor =
=
= 3
Answer:
The average rate of change for f(x) from x=−1 to x = 4 is, 1
Step-by-step explanation:
Average rate A(x) of change for a function f(x) over [a, b] is given by:
![A(x) = \frac{f(b)-f(a)}{b-a}](https://tex.z-dn.net/?f=A%28x%29%20%3D%20%5Cfrac%7Bf%28b%29-f%28a%29%7D%7Bb-a%7D)
As per the statement:
![f(x) = x^2-2x-4](https://tex.z-dn.net/?f=f%28x%29%20%3D%20x%5E2-2x-4)
we have to find the average rate of change from x = -1 to x = 4
At x = -1
![f(-1) = (-1)^2-2(-1)-4 = 1+2-4 = -1](https://tex.z-dn.net/?f=f%28-1%29%20%3D%20%28-1%29%5E2-2%28-1%29-4%20%3D%201%2B2-4%20%3D%20-1)
and
at x = 4
![f(4) = (4)^2-2(4)-4 = 16-8-4 = 4](https://tex.z-dn.net/?f=f%284%29%20%3D%20%284%29%5E2-2%284%29-4%20%3D%2016-8-4%20%3D%204)
Substitute these in [1] we have;
![A(x) = \frac{f(4)-f(-1)}{4-(-1)}](https://tex.z-dn.net/?f=A%28x%29%20%3D%20%5Cfrac%7Bf%284%29-f%28-1%29%7D%7B4-%28-1%29%7D)
⇒![A(x) = \frac{4-(-1)}{4+1}](https://tex.z-dn.net/?f=A%28x%29%20%3D%20%5Cfrac%7B4-%28-1%29%7D%7B4%2B1%7D)
⇒![A(x) = \frac{5}{5}](https://tex.z-dn.net/?f=A%28x%29%20%3D%20%5Cfrac%7B5%7D%7B5%7D)
Simplify:
A(x) = 1
Therefore, the average rate of change for f(x) from x=−1 to x = 4 is, 1